2014
DOI: 10.1111/cobi.12350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Invasive Plants on Arthropods

Abstract: Non-native plants have invaded nearly all ecosystems and represent a major component of global ecological change. Plant invasions frequently change the composition and structure of vegetation communities, which can alter animal communities and ecosystem processes. We reviewed 87 articles published in the peer-reviewed literature to evaluate responses of arthropod communities and functional groups to non-native invasive plants. Total abundance of arthropods decreased in 62% of studies and increased in 15%. Taxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
148
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(172 citation statements)
references
References 109 publications
12
148
1
Order By: Relevance
“…Loss in some arthropod species in invaded sites may therefore be independent of changes in plant diversity, vegetation structure and microclimatic conditions (see Litt et al 2014). These changes would be worth exploring in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss in some arthropod species in invaded sites may therefore be independent of changes in plant diversity, vegetation structure and microclimatic conditions (see Litt et al 2014). These changes would be worth exploring in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Dense stands of IAPs also lead to a decline in soil seed banks of riparian systems (Vosse et al 2008), increasing the probability of extinctions of native species. In addition, IAPs greatly increase biomass (Milton, 1981), affect fire regimes (Van Wilgen et al 2008), change nutrient cycles (Witkowski 1991) and reduce arthropod richness (reviewed by Litt et al 2014). …”
mentioning
confidence: 99%
“…shown a negative impact of neophytes on insects (Tallamy 2004;Casagrande and Dacey 2007;Keeler and Chew 2008;Tallamy et al 2010;Fortuna et al 2013), which is confirmed by meta-analyses showing that non-invaded habitats, in comparison to habitats with a high proportion of alien species, had higher total abundance and taxonomic richness of arthropods (Bezemer et al 2014;van Hengstum et al 2014;Litt et al 2014). In situations where the optimal host is a rare species or there is high competition for food, the cost of feeding on the optimal host may be large enough for an insect that it favours the strategy of increasing the number of potential host plants by utilising a new species (Mayhew 1997).…”
mentioning
confidence: 67%
“…heavy mowing, our study design precluded an assessment of this mechanism. Litt et al (2014) reviewed the literature concerning effects of invasive plants on arthropods. They found that the abundance and richness of ant species decreased with invasion of various plants (including goldenrod, see Lenda et al 2013) in almost 50 % of recent studies and increased in only 7 %.…”
Section: Discussionmentioning
confidence: 99%
“…Goldenrod is a strongly melliferous plant, but the time of flowering is probably too short and too late to provide enough food for invertebrates (Moroń et al 2009). Moreover, an overall decline in species richness and densities of different groups of invertebrates in areas with goldenrod (de Groot et al 2007;Skórka et al 2007;Moroń et al 2009;Fenesi et al 2015) may cause a decrease in the amount of available food for carnivorous ant species (Litt et al 2014), mainly M. scabrinodis. Many species of ants also feed on the honeydew produced by aphids.…”
Section: Discussionmentioning
confidence: 99%